Qualidade da analgesia utilizando bloqueio femoral por injeçãoúnica com ropivacaína ou bupivacaína para as operações dereconstrução do ligamento cruzado anterior e de implante de prótese total dejoelho - Rodrigo de Lima e Souza (2007)
The greatest orthopedical operations are characterized by the hard postoperative pain control. Thus, the femoral block (FB) has been used in several cases around the world, effectively promoting the inferior member analgesia, safety and few side effects. Based upon it, the present study evaluated the quality of analgesia in 90 patients undertaken to surgeries of anterior cruciate ligament repair and of total knee prosthesis implant, having been randomily distributed in three groups: ropivacainegroup, composed of 32 patients undertaken to FB with ropivacaine at 0,25%, bupivacaine group, composed of 30 patients undertaken to FB with bupivacaine at 0,25% and control group, composed of 28 patients who received continuous oral and vein analgesia with non esteroids anti-inflammatory and opioids without FB. According to the verbal scale of pain, evaluated at rest, the incidence of moderate or intense painwas higher in the control group than in the ropivacaine and bupivacaine groups, in the times T1 (until 6 hours after the FB; p = 0,002) and T2 (between 6 and 10 hours after FB; p = 0,001). Not only at rest, but also in motion was moderate or intense pain higher in the control group than in the ropivacaine or bupivacaine, in times T1 (p = 0,001) and T2 (p = 0,000). In relation to the satisfaction with postoperative analgesia, the controlgroup mentioned lower satisfaction when compared to the ropivacaine orbupivacaine in times T2 (p = 0,001) and T3 (after 10 hours and until 24 hours after FB; p = 0,047). Concerning the necessity for opioids, the control group patients presented in time T2 higher consume of opioids than the patients undertaken to FB (p = 0,03). So, concluded by unique bupivacaine injection at 0,25% or ropivacaine at 0,25% in the FB presented better quality of analgesia and higher satisfaction, when compared to the patients of the control group, after the surgeries of reconstruction of the crossed anterior ligament and of the total knee prosthesis implant. Between the ropivacaine and bupivacaine groups there has been no difference in relation to the quality and satisfaction with postoperative analgesia. So, FB with bupivacaine is longer than FBwith ropivacaine (p< 0,05).